STUDI SIFAT MEKANIK KOMPOSIT HIBRID EPOKSI/CLAY/SERAT GELAS - , Heribertus Sukarja, ST, Dr. Kusmono, ST., MT. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The aim of this study is to evaluate the effect of addition of clay on the tensile strength, bending strength and bending modulus of elasticity, impact strength and fracture toughness of hybrid composites epoxy/clay/glass fiber. This study used epoxy for matrix material, clay and glass fibers woven roving types as reinforcement and polyaminoamide as catalist. Handy lay-up method was used for sample preparation. At first the clay was heated at 80 Â° C for 1 hour at the oven is done to reduce the water content of clay. Epoxy mixed with clay variations of 0, 1, 2, 3, 4 and 5 wt%. Mixed using a mechanical Stirrer for 120 minutes with a round of 800 rpm at 80Â°C. The mixtures were cooled for 10 minutes,then put in a vacuum tube for 5 minutes, After that a mixture of clay and epoxy hardener is added again stirred for 5 minutes, then vacuum in the vacuum tube for 3 minutes. Then the matrix is poured into the glass mold, then compressed a glass fiber sheet with roll steel and poured another matrix, the process is repeated up to 4 sheets of glass fiber and then on the roll to a thickness of 3.2 mm.The process then allowed to stand for 24 hours at room temperature, put in heating for 2 hours at a temperature of 125oC and then the specimen was cut with a scroll saw machine into tensile test specimens, bending, impact and fracture toughness. The results show that the addition of clay 1wt% increase mechanical properties, but the addition of clay is more than 1wt% lower tensile strength, bending strength , bending modulus of elasticity and impact strength of hybrid composites of epoxy / clay / glass fiber. Tensile test and bending test and impact test showed that the optimum clay fraction occurs in 1% to increase the tensile strength of 11.52%, 23.52% increase in bending strength and bending modulus of elasticity increase of 7.1%,increase the impact strength of 30.16%. The highest fracture toughness of the composite hybrid epoxy / clay / glass fiber is achieved at 2% clay weight fraction, the fracture toughness increases by 19.09%, but the addition of more than 2% clay weight fraction lower fracture toughness strength.